Make it, don't fake it : leading with authenticity for real business success - Horn, Sabrina (Berrett-Koehler Publishers, 2021)
"Faking it till you make it doesn't work-at least, not long enough to build a sustainable business. This book by a CEO and public relations expert shows how authentic leadership eliminates the need for short-cuts that sabotage success"